Bibliometric study of chemical compounds based on medicinal plants anti-Alzheimer - Fernandes, Idonilton da Conceição; Dalarmi , Luciane; Montrucchio, Deise Prehs; Gaspari Dias , Josiane de Fatima; Miguel , Marilis Dallarmi; Miguel , Obdulio Gomes (Seven Editora, 2023)
Alzheimer’s disease is a chronic neurodegenerative condition that affects mainly memory and other cognitive functions. Interest in finding treatments effective for this disease has increased in recent years, leading to the investigation of the use of medicinal plants and isolated compounds as possible therapeutic treatments. This study aims to identify research on plants and isolated compounds that demonstrate efficacy in the treatment of markers of Alzheimer’s pathology over the years. To achieve this goal, we performed a literature review using methods quantitative, which allows us to identify trends, authors, journals and research areas most relevant to the topic. We collect data and submit them to quantitative analyzes to get an overview of the state of the art in this particular field. The methodology employed included the use of bibliometric software for surveys quantitative surveys and the Rayyan platform for qualitative surveys. The quantitative analysis covered the leadership of the studies, the power analysis used in the articles and the identification of predominant themes. While in the qualitative analysis, we focused on the experimented plants that cause anti-Alzheimer’s effects, with a focus on the isolated chemical compounds responsible by pharmacological action. As a result of the quantitative analysis, we found a growing interest in research on plants and Alzheimer’s disease. Since the first publications at the beginning of the 2000s to the present day, there has been a steady increase in the number of studies, reflecting a significant progress has been made in understanding the possible benefits of plants in the treatment and in preventing this debilitating disease. Our findings highlight the continuing importance of research in this area, which may provide promising therapeutic alternatives to face the challenges posed by the disease of Alzheimer’s. Through this bibliographic research, we hope to contribute to the advancement of scientific knowledge and for the development of more effective therapeutic approaches and accessible for this complex condition. DOI:https://doi.org/10.56238/globalhealthprespesc-039